A novel horizontal subsurface flow constructed wetland: Reducing area requirements and clogging risk. (November 2017) - Tatoulis, Triantafyllos; Akratos, Christos S.; Tekerlekopoulou, Athanasia G.; Vayenas, Dimitrios V.; Stefanakis, Alexandros I.
Abstract: The use of Constructed Wetlands (CWs) has been nowadays expanded from municipal to industrial and agro-industrial wastewaters. The main limitations of CWs remain the relatively high area requirements compared to mechanical treatment technologies and the potential occurrence of the clogging phenomenon. This study presents the findings of an innovative CW design where novel materials were used. Four pilot-scale CW units were designed, built and operated for two years. Each unit consisted of two compartments, the first of which (two thirds of the total unit length) contained either fine gravel (in two units) or random type high density polyethylene (HDPE) (in the other two units). This plastic media type was tested in a CW system for the first time. The second compartment of all four units contained natural zeolite. Two units (one with fine gravel and one with HDPE) were planted with common reeds, while the other two were kept unplanted. Second cheese whey was introduced into the units, which were operated under hydraulic residence times (HRT) of 2 and 4 days. After a two-year operation and monitoring period, pollutant removal rates were approximately 80%, 75% and 90% for COD, ammonium and ortho -phosphate, respectively, while temperature and HRT had no significant effect on pollutant removal. CWs containing the plastic media achieved the same removal rates as those containing gravel, despite receiving three times higher hydraulic surface loads (0.08 m/d) and four times higher organic surface loads (620 g/m 2 /d). This reveals that the use of HDPE plastic media could reduce CW surface area requirements by 75%. Graphical abstract: Highlights: CWs' main drawbacks include substrate media clogging and high area requirements. To minimize clogging and required area of HSF CWs a plastic substrate media was used. The use of plastic substrate increased CW's porosity and hydraulic load by 3 times. Plastic substrate media did not affect CW pollutant removal efficiencies. CWs with plastic substrate media require 75% less area than CWs with gravel.